Subcutaneous Zygomycosis : Current Indian Scenario With A Review - Thappa Devinder Mohan; Karthikeyan Kaliaperumal; Sujatha S (Wolters Kluwer Medknow Publications, 2003)
Zygomycosis broadly consists of mucormycosis and subcutaneous zygomycosis. Subcutaneous zygomycosis can further be subdivided into conidiobolomycosis and basidiobolomycosis. We have done retrospective analysis of data of cases of subcutaneous zygomycosis (basidiobolomycosis), diagnosis based on clinical features, histopathology and/or culture. The cases were treated in Dermatology and STD department of Jawaharlal Institute of postgraduate Medical Education and Research (JIPMER), Pondicherry between 1990 to 2002. Case reported in India has been summarized and relevant literature on this entity has been reviewed.